ANTI-PEPTIC ULCER ACTIVITY OF MUKTASHUKTI BHASMA - Choudhary, Raghuveer; Chouhan, Omi; Gehlot, Anusuya; Rathore, Rajkumar (Pakistan Journal of Physiology, 2010)
Background: Pearl oyster is found at Atlantic and Indian Ocean coasts. Its ash or paste is used in ancient Ayurvedic medicine to manage various gastric disorders. Muktashukti Bhasma (Pearl Oyster Shell) is the calcinated shell of pearl oyster and has calcium, magnesium and iron. It is well known for its antacid and digestive properties. We carried out this study to investigate anti-peptic ulcer activity of Muktashukti Bhasma (MSB). Methods: Two hundred and thirty-eight inbred Albino rats of either sex were divided into 7 groups. Group-I (n=10) was control group, it was kept on distilled water. Suspension of Muktasukti Bhasma (MSB) was administered orally 100 mg/kg body wt. in group-II (n=6), 300 mg/kg body wt. in Group-III (n=6), and 1,000 mg/kg body wt. in Group-IV (n=6). In rest 3 groups (in all n=6) Ranitidine was administered subcutaneously at 0.5 mg/kg body wt. in Group-V, 2 mg/kg in Group-VI, and 5 mg/kg in Group-VII. All the Rats were sacrificed at the end of 19 hours after operation for pyloric ligation and gastric secretions were analyzed for pH, free acidity, and pepsin activity. Result: Muktashukti Bhasma caused reduction in ulcer score and ulcer index with all the doses. MSB caused significant reduction (p<0.001) in free and total acidity, and acid output only at 300 and 1,000 mg/kg dose. MSB and Ranitidine caused decrease in peptic activity at all dose levels. MSB also raised pH. Conclusion: Muktashukti Bhasma shows variable reduction in free and total acidity, acid output and peptic activity.